2016
DOI: 10.1155/2016/2634104
|View full text |Cite
|
Sign up to set email alerts
|

Deposition of Ibuprofen Crystals on Hydroxypropyl Cellulose/Polyacrylamide Gel: Experimental and Mathematic Modeling Releasing

Abstract: The crystallization of nonsteroidal anti-inflammatory drug [2-(4-isobutyl-phenyl) propionic acid] ibuprofen (IBP) on a hydroxypropyl cellulose (HPC) and polyacrylamide (PAAm) gel was studied as well as the release kinetics of the drug. The IBP was crystallized on the gel surface of HPC/PAAm. It had a prismatic shape and the growth was made in an aqueous medium; the crystallinity grade of the gels HPC/PAAm and HPC/PAAm-IBU increased to 68% and to 58%, respectively. The release of IBP is performed by two means: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 22 publications
0
8
0
1
Order By: Relevance
“…According to [33], fully miscible systems of two compounds present a single T g , even when each compound in the composite has its own T g . Similarly, Castillo-Miranda et al [3] reported a single exothermic peak, corresponding to the melting point of the active substance, in a DSC thermogram of HPC/PAAm gel with incorporated International Journal of Polymer Science ibuprofen. This supports the statement that acetaminophen was correctly incorporated into the HPC/PAAm gel, previously established based on the FTIR results.…”
Section: Resultsmentioning
confidence: 82%
See 4 more Smart Citations
“…According to [33], fully miscible systems of two compounds present a single T g , even when each compound in the composite has its own T g . Similarly, Castillo-Miranda et al [3] reported a single exothermic peak, corresponding to the melting point of the active substance, in a DSC thermogram of HPC/PAAm gel with incorporated International Journal of Polymer Science ibuprofen. This supports the statement that acetaminophen was correctly incorporated into the HPC/PAAm gel, previously established based on the FTIR results.…”
Section: Resultsmentioning
confidence: 82%
“…Castillo-Miranda et al [3] modelled ibuprofen release in HPC/PAAm gel by the traditional methods (Equations (1)-(4)), and the best adjustments were obtained with the Korsmeyer-Peppas model, meaning that the release of drug in HPC/PAAm gel occurred through the viscoelastic relaxation of the polymer, as a non-Fickian phenomenon. Therefore, it was decided to model the acetaminophen release in HPC/PAAm gel with the Korsmeyer-Peppas model, assuming that acetaminophen release would also occur through the viscoelastic relaxation of the polymer, since the hydrogel used as DDS was the same.…”
Section: Release Testsmentioning
confidence: 99%
See 3 more Smart Citations